ENTEROVIRUSES DISEASES MODELING IN LABORATORY MICE WITH DYSBIOSIS - V. A. Ponyatovsky; V. V. Bobyr; V. B. Nastenko (Bogomolets National Medical University, 2015)
Summary. The experimental work is devoted to modeling the enteroviral infections in animals with dysbiotic dysfunctions of intestine. As enterovirus, a vaccine strain of serotype 2 poliovirus was selected. The white 30 days old mice of Balb/c line that passed acclimatization were taken as an experimental model. Dysbiosis was formed by oral injection of combination of antibacterial preparations ampicillin and metronidazole in doses of 5, 10 and 20 mg/animal a day. The results of the researches showed that after oral injection of complex of ampicillin and metronidazole in laboratory animals formed pronounced dysbiosis. The optimum dose for modeling dysbiosis with these preparations was determined as 10 mg/animal. It was established that increasing the dose of antibacterial preparations does not impact on depth of dysbiotic displays in mice's intestine and occurs only in decreased animal's body weight. In addition, it is experimentally proved that the development of dysbiosis in mice promotes more rapid release of intestinal type 2 poliovirus. The term of virus's evacuation in such animals lasted for 5-6 days, while in control group it took up to 10 days. It is suggested that bacterial cells might "mask" the viruses from the factors of immune protection and decrease of number of bacteria in the intestine after antibiotic therapy accelerates the ongoing release of the organism from viral antigens. It is possible that viruses are able to establish "symbiotic" relations with bacteria and, thus, stay longer in the intestine of animals, although, obviously there are other factors that affect the rate of excretion of viral antigens from animals' organisms.